Landscape heterogeneity increases survival of Pinus caribaea var. hondurensis juveniles in a frequently burned, humid savanna. (25th March 2022) - Fill, Jennifer M.; Tricone, Fanny; Muschamp, Mario; Crandall, Raelene M.; Anderson, Rick
Abstract: We characterized Caribbean pine ( Pinus caribaea var. hondurensis ) seedling and juvenile survival in lowland Belizean savannas with respect to environment and fire regimes. Plants in open and densely wooded environments had lower survival after fire. We hypothesize that facilitative or correlative mechanisms might promote positive relationships between shrubs and pine survival. Abstract in Spanish is available with online material. Abstract : We tagged and measured the heights of Caribbean pine ( Pinus caribaea var. hondurensis ) juvenile (<2.5 cm diameter at breast height (DBH)) pines over three years in open, shrubby, and densely wooded savanna environments to assess survival across years with and without fire. We assessed char heights on trees after fire to estimate relative fire intensity. Plants in open and densely wooded environments had lower survival after fire than in the absence of fire; there were no differences in survival with or without fire in shrubby plots, where fire behavior was more variable. Resumen: Caracterizamos la supervivencia del pino caribeño ( Pinus caribaea var. hondurensis ) juvenil en las sabanas de las tierras bajas de Belice con respecto al medio ambiente y los regímenes de incendios. Las plantas en ambientes abiertos y densamente boscosos tuvieron una menor supervivencia después de un incendio. Hipotetizamos que los mecanismos facilitadores o correlativos podrían promover relaciones positivas entre los arbustos y la supervivencia de los pinos.